High-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material and preparation method thereof

Through the design of hyperbranched epoxy resin and carbon fiber composite with imide structure, combined with thiol-olefin click reaction and alkaline alcohol solution degradation technology, the thermoset epoxy resin-carbon fiber composite material is solved in the recycling and recycling of thermosetting epoxy resin-carbon fiber composite material. Performance damage and difficult degradation problems have achieved high mechanical properties and degradation efficiency composite materials, suitable for high-end applications.

CN119285900AActive Publication Date: 2025-01-10SOUTH CENTRAL UNIVERSITY FOR NATIONALITIES

Patent Information

Application Number
CN202411161273.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-01-10
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The existing thermosetting epoxy resin-carbon fiber composites have problems of performance damage and difficulty in degradation in recycling and recycling, and their mechanical strength and chemical resistance need to be further improved.

Method used

Hyperbranched epoxy resin with imide structure and carbon fiber composite material, through the reaction of diamino compounds, triac anhydride compounds and thiol-olefin click reaction, a high-performance degradable imide framework superbranch is prepared The epoxy resin is degraded and the material is recovered and reused by alkaline alcohol solution.

Benefits of technology

Composite materials that achieve high mechanical properties, degradation efficiency and recycling functions can effectively degrade under alkaline conditions, maintain the high tensile strength of composite materials, and are suitable for wind power blades and aerospace fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005006496080000021
    Figure BDA0005006496080000021
  • Figure BDA0005006496080000022
    Figure BDA0005006496080000022
  • Figure BDA0005006496080000023
    Figure BDA0005006496080000023
Patent Text Reader

Abstract

The invention relates to the technical field of degradable hyperbranched epoxy resin-carbon fiber composite materials, and particularly discloses a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material and a preparation method thereof. The specific preparation process is as follows: (1) firstly synthesizing an imide skeleton-terminated sulfydryl hyperbranched polymer and hyperbranched epoxy resin; (2) chemically grafting carbon fiber cloth on the surface of the sulfydryl-terminated hyperbranched polymer to obtain modified carbon fiber cloth; and (3) fully infiltrating the modified carbon fiber cloth by blending hyperbranched epoxy resin and E51, and laminating, compounding and curing to obtain the high-strength and degradable epoxy resin-carbon fiber composite material. The composite material can be completely degraded in an alkaline alcohol solution, so that the carbon fiber is recycled and reused. The process is simple, and the composite material has high performance, high degradation efficiency and a recycling function and is expected to be used for manufacturing structural parts in the fields of wind power blades, aerospace and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of degradable hyperbranched epoxy resin-carbon fiber composite materials, and in particular to a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material and a preparation method thereof. Background Art

[0002] Carbon fiber / epoxy resin composites have the advantages of light weight, high strength, good heat stability, chemical corrosion resistance, and good dimensional stability. They are increasingly used in aerospace, automotive, wind power and other fields. However, due to the high cross-linking density of thermosetting epoxy resin, the composite material has a certain brittleness, poor resistance to crack propagation, and is difficult to degrade and easily causes pollution. Therefore, how to recycle carbon fiber composite waste has attracted the attention of more and more researchers. Due to the irreversible cross-linking network, efficient closed-loop recycling of thermosetting resins and carbon fibers without reducing performance has become a major challenge.

[0003] Traditional mechanical recycling methods and chemical recycling methods will inevitably damage the performance and size of carbon fibers. Dynamic covalent polymers with certain environmental stimulus responsiveness have been proposed as a sustainable alternative to non-recyclable thermosetting materials. The introduction of dynamic covalent bonds such as imides, acetals and esters into the polymer backbone enables the degradation / dissolution or reuse of thermosetting epoxy resin materials. The imide structure not only has good degradability under alkaline conditions, but also has outstanding thermal stability, corrosion resistance and high mechanical properties. For this reason, the inventors of this application introduced the imide structure to invent the process technology of degradable hyperbranched epoxy resin (Advanced Materials, 2023, 36; Chemical Engineering Journal 2023, 465) and sulfur-containing degradable hyperbranched epoxy resin (ZL201810387204.3; Composites Part B, 2020, 192, 108005), realizing the recycling and reuse of epoxy resin.

[0004] The irreversible cross-linked structure of thermosetting epoxy resin-carbon fiber composites is difficult to decompose in the recycling of high value-added polymers and carbon fibers, and the mechanical strength of the composites still needs to be improved. Developing a simple and degradable preparation technology for epoxy resin / carbon fiber composites while maintaining the high mechanical strength, high chemical resistance and heat resistance, dimensional stability and durability of the composites is a fundamental way to solve the current problems in this field. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the present invention provides a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material and a preparation method thereof.

[0006] The present invention solves the above technical problems with the following technical solutions:

[0007] Technical solution 1: A high-performance biodegradable imide skeleton hyperbranched epoxy resin, the structural formula of which is shown in general formula (1):

[0008]

[0009] Wherein, R', R", and R'" are the same or different and are independently represented by the structure of general formula (2), general formula (3) or general formula (4):

[0010]

[0011] Wherein, X is one or two of the following structures:

[0012] The structure of R1 is as follows:

[0013]

[0014] R2 is one of the following structures:

[0015]

[0016] R3 is one or more of the following structures:

[0017]

[0018] Technical solution 2: A method for preparing a high-performance biodegradable imide skeleton hyperbranched epoxy resin, comprising the following steps:

[0019] A diamino compound and a triacid anhydride compound are added to a three-necked flask, stirred and reacted at 80-130° C. for 8-12 hours, and then tris(2-hydroxyethyl)isocyanurate (THEIC) is added, and stirred and reacted at 120-180° C. for 10-16 hours to obtain a terminal hydroxyl hyperbranched polymer; mercaptocarboxylic acid and a water-carrying agent are then added, and stirred and reacted at 120-140° C. for 10-16 hours to obtain a terminal mercapto hyperbranched polymer; finally, allyl glycidyl ether (AGE), an organic solvent and a photoinitiator are added to the three-necked flask, and ultraviolet light with a power of 400W-800W is used for irradiation for 30-70 minutes to carry out a thiol-olefin click reaction, and then the organic solvent is removed to obtain a degradable imide skeleton hyperbranched epoxy resin.

[0020] Furthermore, the diamino compound is one or more of 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether (3,4'-ODA), 3,3'-diaminodiphenyl sulfone (DADPS), 4,4'-diaminodiphenyl sulfone (DDS), 2,2'-diaminodiphenyl sulfide (DOA), and 4,4'-diaminodiphenyl sulfide (BAS); the trianhydride compound is trimellitic anhydride (TMA) or 1,2,4-cyclohexanetricarboxylic anhydride (HTMA); and the mercaptocarboxylic acid is one or both of mercaptopropionic acid (MPA) and thioglycolic acid (TGA).

[0021] Furthermore, the molar ratio of the diamino compound, the trianhydride compound, tris(2-hydroxyethyl)isocyanurate, and the mercaptocarboxylic acid is 1:2:(0.9-2):(1.5-8.5), and the molar ratio of the mercaptocarboxylic acid to allyl glycidyl ether is 1:1.

[0022] Furthermore, the water-carrying agent is one or two of toluene and xylene, and its mass is 0.5 to 5 times the mass of tris(2-hydroxyethyl)isocyanurate (THEIC); the organic solvent is one or more of tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, chloroform, N,N-dimethylformamide and dichloromethane, and its mass is 10 to 30 times the mass of tris(2-hydroxyethyl)isocyanurate (THEIC); the photoinitiator is one or more of 4-dimethylaminopyridine, benzophenone, p-aminopropiophenone, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycyclohexyl phenyl ketone, and its mass is 0.4% to 2% of the mass of allyl glycidyl ether (AGE).

[0023] Furthermore, the number average molecular weight of the terminal mercapto group hyperbranched polymer is 1300 to 16000 g / mol.

[0024] Furthermore, the number average molecular weight of the degradable imide skeleton hyperbranched epoxy resin is 1500-19000 g / mol, the epoxy value is 0.10-0.25 mol / 100 g, and the shape factor is 0.97-2.80.

[0025] Technical solution three: A high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material, which is prepared by blending the above-mentioned degradable imide skeleton hyperbranched epoxy resin or the degradable imide skeleton hyperbranched epoxy resin prepared by the above-mentioned method with bisphenol A type epoxy resin and filling it in carbon fiber cloth, and then laminating and curing it. Before curing, the carbon fiber cloth is modified by the above-mentioned terminal thiol hyperbranched polymer through a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth.

[0026] The mass ratio of the carbon fiber cloth, the degradable imide skeleton hyperbranched epoxy resin and the bisphenol A type epoxy resin is 1: (0.1-0.2): (0.2-0.5).

[0027] Technical Solution 4: A method for preparing a high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material, comprising the following steps:

[0028] The carbon fiber cloth is completely immersed in a mixed solution of a terminal thiol hyperbranched polymer, an organic solvent and a photoinitiator, and is irradiated with ultraviolet light of a power of 400-800W for 20-60min to carry out a thiol-olefin click reaction; after the reaction is completed, the carbon fiber cloth is taken out and dried at 80-100°C for 5-15h to obtain a surface functionalized carbon fiber cloth (TCF); the TCF is placed in a mold, and a mixture of a degradable imide skeleton hyperbranched epoxy resin, a bisphenol A type epoxy resin and a curing agent is evenly applied to the TCF in the mold, and hot-pressed and cured for 1-3h under the conditions of 2-10MPa and 100-180°C; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 5-15MPa for 10-20min, and then the temperature is lowered to below 80°C and taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material.

[0029] Furthermore, the carbon fiber cloth is one of commercially available T300, T700 and T800; the number average molecular weight of the terminal mercapto hyperbranched polymer is 1300-16000 g / mol, and its mass is 0.5-2.0 times the mass of the carbon fiber cloth.

[0030] Furthermore, the photoinitiator is one or more of 4-dimethylaminopyridine, benzophenone, p-aminopropiophenone, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycyclohexyl phenyl ketone, and its mass is 0.5% to 3% of the mass of the carbon fiber cloth; the organic solvent is one or more of tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, chloroform, N,N-dimethylformamide and dichloromethane, and its mass is 0.5 to 30 times the mass of the carbon fiber cloth.

[0031] Furthermore, the number average molecular weight of the degradable imide skeleton hyperbranched epoxy resin is 1500-19000 g / mol, the epoxy value is 0.10-0.25 mol / 100 g, and the shape factor is 0.97-2.80. The mass ratio of the TCF, the degradable imide skeleton hyperbranched epoxy resin, the bisphenol A type epoxy resin, and the curing agent is 1: (0.1-0.2): (0.2-0.5): (0.05-0.1).

[0032] Furthermore, the bisphenol A epoxy resin model is E51.

[0033] Furthermore, the curing agent is one or more of 4,4'-diaminodiphenyl ether (ODA), 3,4'-diaminodiphenyl ether (3,4'-ODA), 3,3'-diaminodiphenyl sulfone (DADPS), 4,4'-diaminodiphenyl sulfone (DDS), 2,2'-diaminodiphenyl sulfide (DOA), and 4,4'-diaminodiphenyl sulfide (BAS).

[0034] Technical Solution 5: The degradation and recycling method of the above-mentioned high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material comprises the following steps:

[0035] The degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material is immersed in an alkaline alcohol solution, and degraded at 130-180°C for 2-12 hours to obtain a carbon fiber cloth and a degradation liquid; the carbon fiber cloth is rinsed with acetone and dried at 50-70°C for 10-24 hours to obtain a regenerated carbon fiber cloth; the degradation liquid is filtered and separated to obtain a filter residue, and the filtered filter residue is purified by column chromatography to obtain a recovered diamine monomer.

[0036] Afterwards, the recycled carbon fiber cloth is completely immersed in a mixed solution of a terminal thiol hyperbranched polymer, an organic solvent and a photoinitiator, and is irradiated with ultraviolet light with a power of 400-800W for 20-60 minutes to carry out a thiol-olefin click reaction; after the reaction is completed, the carbon fiber cloth is taken out, and dried at 80-100°C for 5-15 hours to obtain a surface-functionalized recycled carbon fiber cloth; the recycled carbon fiber cloth is put into a mold, and a mixture of a degradable imide skeleton hyperbranched epoxy resin, a bisphenol A type epoxy resin and a curing agent is evenly applied to the surface of the recycled carbon fiber cloth in the mold, and hot-pressed and cured for 1-3 hours under the conditions of 2-10MPa and 100-180°C; after the hot pressing is completed, the heating is stopped, and the laminate is pressed at 5-15MPa for 10-20 minutes, and then the temperature is reduced to 80°C and taken out, so that the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material can be realized.

[0037] Further, the concentration of the alkaline alcohol solution is 0.10-1.50 mol / L, the alkaline alcohol solution is an alcohol solution of potassium hydroxide and / or sodium hydroxide, the alcohol in the alkaline alcohol solution is methanol and / or ethanol, and the mass proportion of alcohol in the alkaline alcohol solution is 90%-100%. The alkaline alcohol solution can be, for example: a methanol aqueous solution of potassium hydroxide, a methanol solution of potassium hydroxide, an ethanol aqueous solution of potassium hydroxide, an ethanol solution of potassium hydroxide, a methanol solution of sodium hydroxide, a methanol aqueous solution of sodium hydroxide, an ethanol aqueous solution of sodium hydroxide, an ethanol solution of sodium hydroxide, etc.

[0038] Furthermore, the mass ratio of the degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material to the alkaline alcohol solution is (3-5): (10-20).

[0039] Furthermore, the regenerated carbon fiber cloth obtained after the degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material is degraded by an alkaline alcohol solution has a surface that is similar to that of the original carbon fiber cloth and the tensile properties of the composite material synthesized therewith, and can be used as a new carbon fiber cloth to continue synthesizing the degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material.

[0040] Compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:

[0041] 1. The present invention synthesizes a hyperbranched epoxy resin containing an imide structure, and tests the shape factor of the hyperbranched epoxy resin by dynamic and static light scattering techniques, thereby realizing that the epoxy resin has a spherical hyperbranched topological structure.

[0042] 2. The present invention obtains a method for clicking chemistry carbon fiber cloth with terminal thiol hyperbranched polymer. The introduction of hyperbranched topological structure can significantly improve the interfacial interaction between carbon fiber and epoxy resin. The deformable hyperbranched topological structure can effectively disperse and transfer loads, effectively improve the mechanical properties of the composite material, and obtain a high-strength epoxy resin-carbon fiber composite material.

[0043] 3. The present invention blends the hyperbranched epoxy resin with the bisphenol A epoxy resin having a linear structure, thereby increasing the polarity of the system, improving the compatibility, and effectively improving the mechanical properties of the composite material.

[0044] 4. The present invention utilizes low-end carbon fiber cloth (such as T300) and epoxy resin composite material to obtain the tensile strength of high-end carbon fiber cloth (such as T700 and T800).

[0045] 5. The hyperbranched epoxy resin-carbon fiber cloth composite material of the present invention has high performance, high degradation efficiency and recycling and reuse functions, and is expected to be used in the manufacture of structural parts in the fields of wind turbine blades, aerospace, etc.

[0046] 6. The preparation process of the degradable imide skeleton hyperbranched epoxy resin-carbon fiber cloth composite material of the present invention is simple, the reaction conditions are mild, the reaction time is short, the raw material cost is low, and degradation and recovery can be achieved under alkaline alcohol solution conditions, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 These are SEM images of the raw carbon fiber cloth T800 (a) in Example 6 and the regenerated carbon fiber cloth (b) obtained after soaking in an alkaline alcohol solution.

[0048] The surface of the recycled carbon fiber is not much different from the original carbon fiber, with several black spots similar to defects appearing. Its single-filament tensile strength is slightly lower than that before recycling, which may be because the intermediate steps cause more microcracks on the carbon fiber surface. DETAILED DESCRIPTION

[0049] The method of the present invention is further described below in conjunction with specific examples, but these examples should not limit the scope of protection of the present invention in any way.

[0050] The raw material carbon fiber cloth used in the embodiments and comparative examples is one of the commercially available T300, T700 and T800, wherein T300 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF220T, T700 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF200T, and T800 was purchased from Anqing Kawi Technology Co., Ltd. with a specification of KCF260T.

[0051] The bisphenol A epoxy resin used in the examples and comparative examples is commercial E51.

[0052] The purity of methanol used for the degradation of the composite material in the embodiment and the comparative example is 99.9%, and the purity of ethanol is 99.9%.

[0053] Example 1 A high-performance biodegradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material and a preparation method thereof, wherein the steps are as follows:

[0054] (1) Synthesis of hyperbranched epoxy resin

[0055] 2.00 g (10 mmol) ODA and 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 80° C. for 12 h, and then 5.22 g (20 mmol) THEIC was added, and stirred and reacted at 120° C. for 16 h to obtain a terminal hydroxyl hyperbranched polymer; 1.59 g (15 mmol) MPA and 2.61 g toluene were added to the flask, and the stirring reaction was continued at 120° C. for 16 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-3, where the number 3 is the number of terminal thiol groups, determined by nuclear magnetic resonance to determine the grafting rate, the same below, no further description), the number average molecular weight of which is shown in Table 1; finally, 1.71 g (15 mmol) AGE, 0.03 g benzophenone and 52.20 g 1,4-Dioxane was irradiated with ultraviolet light at a power of 400 W for 70 min to undergo a thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-3), the properties of which are shown in Table 2.

[0056] (2) Preparation of composite materials

[0057] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 1.50 g of SH-HBP-3, 1.50 g of tetrahydrofuran and 0.02 g of benzophenone, and irradiated with ultraviolet light of 400 W for 60 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 1-TCF. The 1-TCF was taken out and dried at 80 ° C for 15 h. The 3.00 g of 1-TCF after drying was put into a mold, and 0.30 g of HEP-3, 1.50 g of bisphenol A epoxy resin and 0.15 g of The ODA mixture was evenly applied to the 1-TCF in the mold and hot-pressed and cured at 100°C for 3 h under 2 MPa conditions. After the hot pressing was completed, the heating was stopped and the laminated at 5 MPa for 20 min. When the temperature dropped to 80°C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material (hereinafter referred to as a composite material for the sake of simplicity of description, the same below), and its tensile strength is shown in Table 3.

[0058] (3) Degradation and recycling of composite materials

[0059] 5.00g of the composite material was immersed in 10.00g of 1.50mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and degraded at 130°C for 12h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 50°C for 24h to obtain a regenerated carbon fiber cloth; then 1.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 0.75g SH-HBP-3, 0.75g tetrahydrofuran and 0.01g benzophenone, and irradiated with ultraviolet light at a power of 400W for 60min to carry out a thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 80°C for 15h to obtain a surface-functionalized regenerated carbon fiber cloth; the dried 1.50g of the surface-functionalized regenerated carbon fiber cloth was put into a mold, and 0.15g HEP-3, 0.75g bisphenol A epoxy resin and 0.075g The ODA mixture is evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 100°C for 3 hours under 2MPa conditions. After the hot pressing is completed, the heating is stopped, and the laminate is pressed at 5MPa for 20 minutes. When the temperature reaches 80°C, it is taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material can be achieved. The tensile strength is shown in Table 3.

[0060] Example 2 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0061] (1) Synthesis of hyperbranched epoxy resin

[0062] 1.00 g (5 mmol) 3,4'-ODA, 1.00 g (5 mmol) ODA, and 3.96 g (20 mmol) HTMA were added to a three-necked flask, stirred and reacted at 90°C for 11 h, then 4.70 g (18 mmol) THEIC was added, stirred and reacted at 120°C for 16 h to obtain a terminal hydroxyl hyperbranched polymer; 1.84 g (20 mmol) TGA and 4.61 g dihydrogen peroxide were added to the flask. Toluene, continue stirring and reacting at 130°C for 15h to obtain a terminal thiol hyperbranched polymer (SH-HBP-6), whose number average molecular weight is shown in Table 1; finally, 2.28g (20mmol) AGE, 0.01g p-aminopropiophenone and 56.20g ethyl acetate are added to the flask, and irradiated with ultraviolet light at a power of 450W for 60min to carry out a thiol-olefin click reaction, and remove the solvent to obtain a hyperbranched epoxy resin (HEP-6), whose properties are shown in Table 2.

[0063] (2) Preparation of composite materials

[0064] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 1.90 g of SH-HBP-6, 3 g of chloroform, 2 g of acetone, 0.02 g of benzophenone and 0.01 g of 4-dimethylaminopyridine, and irradiated with ultraviolet light at a power of 450 W for 50 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, namely 2-TCF; 2-TCF was taken out and dried in a vacuum oven at 85°C for 14 h; 4.00 g of 2-TCF after drying was taken out and placed in a mold, and 0.49 g A mixture of HEP-6, 1.60 g bisphenol A epoxy resin, 0.15 g ODA and 0.10 g 3,4'-ODA was evenly applied to 2-TCF in the mold and hot-pressed and cured at 110 °C for 3 h under 3 MPa conditions. After the hot pressing was completed, the heating was stopped and the laminated at 6 MPa for 19 min. When the temperature reached 80 °C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0065] (3) Degradation and recycling of composite materials

[0066] 4.00g of the composite material was immersed in a mixed methanol solution of 16.00g of 0.15mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 140°C for 11h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 20h to obtain a regenerated carbon fiber cloth; then 1.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 0.75g SH-HBP-6, 0.75g tetrahydrofuran and 0.01g benzophenone, and irradiated with ultraviolet light with a power of 400W for 60min to carry out a thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 80°C for 15h to obtain a surface functionalized regenerated carbon fiber cloth; 2.00g of the surface functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.245g HEP-6, 0.80g bisphenol A epoxy resin, 0.075g ODA and 0.05g The mixture of 3,4'-ODA is evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 110°C for 3 h under 3 MPa conditions; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 6 MPa for 19 min. When the temperature reaches 80°C, it is taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material can be achieved. The tensile strength is shown in Table 3.

[0067] Example 3 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0068] (1) Synthesis of hyperbranched epoxy resin

[0069] 2.48 g (10 mmol) of DADPS and 3.96 g (20 mmol) of HTMA were added to a three-necked flask, stirred and reacted at 100° C. for 10 h, and then 3.92 g (15 mmol) of THEIC was added, and stirred and reacted at 140° C. for 14 h to obtain a terminal hydroxyl hyperbranched polymer; 2.97 g (28 mmol) of MPA and 4.61 g of xylene and 3 g of toluene were added to the flask, and the stirring reaction was continued at 130° C. for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-8), whose number average molecular weight is shown in Table 1; finally, 3.20 g (28 mmol) of AGE, 0.01 g of p-aminopropiophenone, 0.02 g of 4-dimethylaminopyridine, and 0.01 g of 2,2-Dimethoxy-2-phenylacetophenone, 56.20 g of ethyl acetate and 10.28 g of acetone were irradiated with ultraviolet light at a power of 500 W for 50 min to carry out a thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-8), the properties of which are shown in Table 2.

[0070] (2) Preparation of composite materials

[0071] 3.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 3.01 g SH-HBP-8, 3 g chloroform, 2 g acetone, 10 g N,N-dimethylformamide, 0.02 g benzophenone, 0.01 g 4-dimethylaminopyridine and 0.01 g p-aminopropiophenone, and irradiated with ultraviolet light of 550 W for 45 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 3-TCF; 3-TCF was taken out and dried in a vacuum oven at 90 ° C for 12 h; 4.00 g of 3-TCF after drying was taken out and put into a mold, and 0.49 g HEP-8, 1.70 g bisphenol A epoxy resin, 0.15 g ODA, 0.1 g DDS and 0.10 g The mixture of 3,4'-ODA was evenly applied to 3-TCF in the mold and hot-pressed and cured at 130°C for 2 h under 5 MPa conditions. After the hot pressing was completed, the heating was stopped and the laminated at 7 MPa for 17 min. When the temperature reached 80°C, it was taken out to obtain a high-performance biodegradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0072] (3) Degradation and recycling of composite materials

[0073] 4.00g of the composite material was immersed in a mixed solution of 15.00g of 0.32mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol) in ethanol and methanol (ethanol: methanol = 1:1, m / m), and degraded at 150°C for 10h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 60°C for 18h to obtain a regenerated carbon fiber cloth; then 1.50g of the regenerated carbon fiber cloth was completely immersed in 1.505g of SH-HBP-8, 1.50g of chloroform, 1.00g of acetone, 5.00g of N,N-dimethylformamide, 0.01g of benzophenone and 0.005g of The mixed solution of 4-dimethylaminopyridine and 0.005g p-aminopropiophenone was irradiated with ultraviolet light of 550W for 45min to carry out thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 90℃ for 12h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g surface functionalized regenerated carbon fiber cloth after drying was put into the mold, and a mixture of 0.245g HEP-8, 0.85g bisphenol A epoxy resin, 0.075g ODA, 0.05g DDS and 0.05g 3,4'-ODA was evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot-pressed and cured at 130℃ for 2h under 5MPa; after the hot pressing was completed, the heating was stopped, and the laminated at 7MPa for 17min, and the temperature was taken out when it reached 80℃, and the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite materials could be realized, and the tensile strength thereof is shown in Table 3.

[0074] Example 4 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0075] (1) Synthesis of hyperbranched epoxy resin

[0076] 1.24 g (5 mmol) DADPS, 1.00 g (5 mmol) ODA, and 3.96 g (20 mmol) HTMA were added to a three-necked flask, stirred and reacted at 110° C. for 9 h, and then 3.13 g (12 mmol) THEIC was added, and stirred and reacted at 150° C. for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 1.01 g (11 mmol) TGA, 2.65 g (25 mmol) MPA, 5.01 g xylene, and 2 g toluene were added to the flask, and the stirring reaction was continued at 130° C. for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-12-I), whose number average molecular weight is shown in Table 1; finally, 4.11 g (36 mmol) AGE, 0.02 g 4-dimethylaminopyridine, and 0.02 g 2,2-Dimethoxy-2-phenylacetophenone, 50.20 g of dichloromethane and 10.98 g of acetone were irradiated with ultraviolet light of 550 W for 40 min to carry out thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-12-I), the properties of which are shown in Table 2.

[0077] (2) Preparation of composite materials

[0078] 4.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 3.33 g of SH-HBP-12-I, 3.14 g of tetrahydrofuran, 2.58 g of acetone, 10.13 g of N,N-dimethylformamide, 0.02 g of 1-hydroxycyclohexyl phenyl ketone, 0.02 g of 4-dimethylaminopyridine, and 0.01 g of p-aminophenylacetone, and irradiated with ultraviolet light of 650 W for 40 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 4-TCF; 4-TCF was taken out and dried at 95° C. for 10 h; 4.00 g of 4-TCF after drying was taken out and placed in a mold, and 0.50 g of HEP-12-I, 1.50 g of bisphenol A epoxy resin, 0.15 g of DOA, 0.1 g of A mixture of DDS and 0.08 g of 3,4'-ODA was evenly applied to the 4-TCF in the mold and hot-pressed at 150 °C for 2 h under 8 MPa. After the hot pressing was completed, the heating was stopped and the laminated at 9 MPa for 15 min. When the temperature reached 80 °C, it was taken out to obtain a high-performance biodegradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0079] (3) Degradation and recycling of composite materials

[0080] 5.00g of the composite material was immersed in a mixed methanol aqueous solution (methanol: water = 9:1, m / m) of 12.00g 0.42mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and degradation solution were obtained after degradation at 155°C for 9h; the carbon fiber cloth was rinsed with acetone and dried at 65°C for 15h to obtain a regenerated carbon fiber cloth; then 2.00g of the regenerated carbon fiber cloth was completely immersed in 1.665g SH-HBP-12-Ⅰ, 1.57g tetrahydrofuran, 1.29g acetone, 5.065g N,N-dimethylformamide, 0.01g 1-hydroxycyclohexylphenyl ketone and 0.01g The mixed solution of 4-dimethylaminopyridine and 0.005g p-aminopropiophenone was irradiated with ultraviolet light of 650W for 40min to carry out thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 95℃ for 10h to obtain surface functionalized recycled carbon fiber cloth; 2.00g surface functionalized recycled carbon fiber cloth after drying was put into the mold, and a mixture of 0.25g HEP-12-Ⅰ, 0.75g bisphenol A epoxy resin, 0.075g DOA, 0.05g DDS and 0.04g 3,4'-ODA was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 150℃ for 2h under 8MPa; after the hot pressing was completed, the heating was stopped, and the laminated at 9MPa for 15min, and the temperature was taken out when it reached 80℃, and the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite materials could be realized, and the tensile strength thereof is shown in Table 3.

[0081] Example 5 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0082] (1) Synthesis of hyperbranched epoxy resin

[0083] 1.08 g (5 mmol) of DOA, 1.08 g (5 mmol) of BAS and 3.84 g (20 mmol) of TMA were added to a three-necked flask, stirred and reacted at 90° C. for 11 h, and then 4.70 g (18 mmol) of THEIC was added, and stirred and reacted at 140° C. for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 3.68 g (40 mmol) of TGA and 11.61 g of xylene were added to the flask, and the stirring reaction was continued at 130° C. for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-15), whose number average molecular weight is shown in Table 1; finally, 4.57 g (40 mmol) of AGE, 0.02 g of p-aminopropiophenone and 66.20 g of ethyl acetate were added to the flask, and ultraviolet light with a power of 450 W was used for 60 min to carry out a thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-15), whose properties are shown in Table 2.

[0084] (2) Preparation of composite materials

[0085] 3.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 1.50 g of SH-HBP-15, 3.00 g of dichloromethane, 10 g of acetone, 0.02 g of benzophenone and 0.01 g of 4-dimethylaminopyridine, and irradiated with ultraviolet light of 450 W for 50 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 5-TCF; 5-TCF was taken out and dried at 85 ° C for 14 h; 4.00 g of 5-TCF after drying was taken out and put into a mold, and 0.48 g of HEP-15, 1.10 g of bisphenol A epoxy resin, 0.10 g of ODA and 0.10 g of The mixture of 3,4'-ODA was evenly applied to 5-TCF in the mold and hot-pressed and cured at 160°C for 2 h under 6 MPa. After the hot pressing was completed, the heating was stopped and the laminated at 10 MPa for 15 min. When the temperature reached 80°C, it was taken out to obtain a high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0086] (3) Degradation and recycling of composite materials

[0087] 4.00g of the composite material was immersed in a mixed methanol aqueous solution (methanol: water = 9:1, m / m) of 17.00g 0.35mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 160°C for 6h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 20h to obtain a regenerated carbon fiber cloth; then 1.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 0.75g SH-HBP-15, 1.50g dichloromethane, 5g acetone, 0.01g benzophenone and 0.005g 4-dimethylaminopyridine, and irradiated with ultraviolet light with a power of 450W for 50min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 85°C for 14h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.24g A mixture of HEP-15, 0.55g bisphenol A epoxy resin, 0.05g ODA and 0.05g 3,4'-ODA was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 160°C for 2h under 6MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 10MPa for 15min. When the temperature reached 80°C, the composite material was taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material was achieved. The tensile strength is shown in Table 3.

[0088] Example 6 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0089] (1) Synthesis of hyperbranched epoxy resin

[0090] 1.24 g (5 mmol) DADPS, 0.65 g (3 mmol) BAS, 0.43 g (2 mmol) DOA, 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 115° C. for 10 h, then 3.13 g (12 mmol) THEIC was added, stirred and reacted at 150° C. for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 2.76 g (30 mmol) TGA, 3.18 g (30 mmol) MPA and 4.10 g xylene and 5.00 g toluene were added to the flask, and the stirring reaction was continued at 135° C. for 11 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-18), the number average molecular weight of which is shown in Table 1; finally 6.85 g (60 mmol) AGE, 0.05 g 1-hydroxycyclohexyl phenyl ketone, 0.04 g p-aminopropiophenone, 0.02 g 2,2-Dimethoxy-2-phenylacetophenone, 12.32 g acetone, 5.12 g tetrahydrofuran and 18.15 g dichloromethane were irradiated with ultraviolet light of 550 W for 65 min to carry out thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-18), the properties of which are shown in Table 2.

[0091] (2) Preparation of composite materials

[0092] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of SH-HBP-18, 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 6-TCF; 6-TCF was taken out and dried at 85° C. for 7 h; 4.00 g of 6-TCF after drying was taken out and put into a mold, and 0.45 g of HEP-18, 0.85 g of bisphenol A epoxy resin, 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the 6-TCF in the mold and hot-pressed and cured at 180°C for 1 h under 9 MPa. After the hot pressing was completed, the heating was stopped and the laminated at 13 MPa for 12 min. When the temperature reached 80°C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0093] (3) Degradation and recycling of composite materials

[0094] 5.00g of the composite material was immersed in 15.00g of 0.11mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and the carbon fiber cloth and degradation solution were obtained after degradation at 160°C for 6h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 19h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.95g SH-HBP-18, 5g acetone, 10g tetrahydrofuran, 40g ethyl acetate, 0.015g benzophenone and 0.015g 4-dimethylaminopyridine, and 0.03g p-aminopropiophenone, and irradiated with ultraviolet light with a power of 750W for 30min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 85°C for 7h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.225g A mixture of HEP-18, 0.425g bisphenol A epoxy resin, 0.03g DADPS, 0.01g DDS, 0.05g ODA and 0.05g BAS was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 9MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 13MPa for 12min. When the temperature reached 80°C, it was taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material was achieved. The tensile strength is shown in Table 3.

[0095] Example 7 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0096] (1) Synthesis of hyperbranched epoxy resin

[0097] 1.24 g (5 mmol) DDS, 0.65 g (3 mmol) DOA, 0.43 g (2 mmol) BAS, 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 120° C. for 9 h, then 2.61 g (10 mmol) THEIC was added, stirred and reacted at 160° C. for 12 h to obtain a terminal hydroxyl hyperbranched polymer; 6.45 g (70 mmol) TGA and 4.10 g xylene and 2.00 g toluene were added to the flask, and the stirring reaction was continued at 140° C. for 10 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-20), the number average molecular weight of which is shown in Table 1; finally 7.99 g (70 mmol) AGE, 0.06 g 1-hydroxycyclohexyl phenyl ketone, 0.05 g p-aminopropiophenone, 0.02 g 2,2-Dimethoxy-2-phenylacetophenone, 12.32 g acetone and 18.15 g dichloromethane were irradiated with ultraviolet light at a power of 600 W for 60 min to carry out a thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-20), the properties of which are shown in Table 2.

[0098] (2) Preparation of composite materials

[0099] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 5.00 g of SH-HBP-20, 40 g of chloroform, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.04 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.05 g of p-aminopropiophenone, and irradiated with ultraviolet light of 800 W for 20 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 7-TCF; 7-TCF was taken out and dried at 90° C. for 6 h; 4.00 g of 7-TCF after drying was taken out and put into a mold, and 0.50 g of HEP-20, 0.80 g of bisphenol A epoxy resin, 0.05 g of DADPS, 0.05 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the 7-TCF in the mold and hot-pressed and cured at 180°C for 1h under 10MPa. After the hot pressing was completed, the heating was stopped and the laminated at 15MPa for 10min. When the temperature dropped to 80°C, it was taken out to obtain a high-performance biodegradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0100] (3) Degradation and recycling of composite materials

[0101] 5.00g of the composite material was immersed in 16.00g of 0.80mol / L potassium hydroxide ethanol solution, and after degradation at 170°C for 4h, a carbon fiber cloth and a degradation solution were obtained; the carbon fiber cloth was rinsed with acetone and dried at 60°C for 18h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 2.50g SH-HBP-20, 20g chloroform, 10g tetrahydrofuran, 40g ethyl acetate, 0.02g benzophenone, 0.015g 4-dimethylaminopyridine, and 0.025g p-aminopropiophenone, and irradiated with ultraviolet light with a power of 800W for 20min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 90°C for 6h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.25g A mixture of HEP-20, 0.40g bisphenol A epoxy resin, 0.025g DADPS, 0.025g DDS, 0.05g ODA and 0.05g BAS was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 10MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 15MPa for 10min. When the temperature reached 80°C, it was taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material was achieved. The tensile strength is shown in Table 3.

[0102] Example 8 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0103] (1) Synthesis of hyperbranched epoxy resin

[0104] 1.24 g (5 mmol) DADPS, 0.65 g (3 mmol) DOA, 0.43 g (2 mmol) BAS, 3.96 g (20 mmol) HTMA were added to a three-necked flask, stirred and reacted at 130° C. for 8 h, then 2.35 g (9 mmol) THEIC was added, stirred and reacted at 180° C. for 10 h to obtain a terminal hydroxyl hyperbranched polymer; 7.83 g (85 mmol) TGA and 4.80 g xylene and 7.00 g toluene were added to the flask, and the stirring reaction was continued at 140° C. for 10 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-24), the number average molecular weight of which is shown in Table 1; finally 9.70 g (85 mmol) AGE, 0.09 g 1-hydroxycyclohexyl phenyl ketone, 0.05 g 4-dimethylaminopyridine, 0.05 g 2,2-Dimethoxy-2-phenylacetophenone, 57.60 g of dichloromethane and 12.90 g of tetrahydrofuran were irradiated with ultraviolet light of 800 W for 30 min to carry out thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-24), the properties of which are shown in Table 2.

[0105] (2) Preparation of composite materials

[0106] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 10.00 g of SH-HBP-24, 50 g of chloroform, 20 g of acetone, 80 g of ethyl acetate, 0.05 g of benzophenone, 0.04 g of 4-dimethylaminopyridine and 0.06 g of p-aminopropiophenone, and irradiated with ultraviolet light of 800 W for 20 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 8-TCF; 8-TCF was taken out and dried at 100 ° C for 5 h; 4.00 g of 8-TCF after drying was taken out and put into a mold, and 0.80 g of HEP-24, 0.80 g of bisphenol A epoxy resin, 0.05 g of ODA, 0.10 g of DDS and 0.10 g of 3,4'-ODA, 0.10 g of The BAS mixture was evenly applied to the 8-TCF in the mold and hot-pressed and cured at 180°C for 1 h under 10 MPa. After the hot pressing was completed, the heating was stopped and the laminated at 15 MPa for 10 min. When the temperature reached 80°C, it was taken out to obtain a high-performance biodegradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0107] (3) Degradation and recycling of composite materials

[0108] 5.00g of the composite material was immersed in a mixed ethanol solution of 20.00g of 0.10mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 180°C for 2h; the carbon fiber cloth was rinsed with acetone and dried at 70°C for 10h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 5.00g SH-HBP-24, 25g chloroform, 10g acetone, 40g ethyl acetate, 0.025g benzophenone and 0.02g 4-dimethylaminopyridine, and 0.03g p-aminopropiophenone, and irradiated with ultraviolet light with a power of 800W for 20min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 100°C for 5h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.40g A mixture of HEP-24, 0.40g bisphenol A epoxy resin, 0.025g ODA, 0.05g DDS, 0.05g 3,4'-ODA and 0.05g BAS was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 10MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 15MPa for 10min. When the temperature reached 80°C, the composite material was taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material was achieved. The tensile strength is shown in Table 3.

[0109] Example 9 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0110] (1) Preparation of composite materials

[0111] 4.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.33 g of SH-HBP-12-Ⅰ (prepared in Example 4), 3.14 g of tetrahydrofuran, 2.58 g of acetone, 10.13 g of N,N-dimethylformamide, 0.02 g of 1-hydroxycyclohexyl phenyl ketone, 0.02 g of 4-dimethylaminopyridine, and 0.01 g of p-aminopropiophenone, and irradiated with ultraviolet light of 650 W for 40 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 9-TCF; 9-TCF was taken out and dried at 95° C. for 10 h; 4.00 g of 9-TCF after drying was taken out and placed in a mold, and 0.50 g of HEP-12-Ⅰ (prepared in Example 4), 1.50 g of bisphenol A epoxy resin, 0.15 g of DOA, 0.1 g of A mixture of DDS and 0.08 g of 3,4'-ODA was evenly applied to 9-TCF in the mold and hot-pressed at 150 °C for 2 h under 8 MPa conditions. After the hot pressing was completed, heating was stopped and lamination was performed at 9 MPa for 15 min. When the temperature reached 80 °C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0112] (2) Degradation and recycling of composite materials

[0113] 5.00 g of the composite material was immersed in a mixed methanol water (methanol: water = 9:1, m / m) solution of 12.00 g of 0.42 mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 155°C for 9 h; the carbon fiber cloth was rinsed with acetone and dried at 65°C for 15 h to obtain a regenerated carbon fiber cloth; then 2.00 g of the regenerated carbon fiber cloth was completely immersed in 1.665 g of SH-HBP-12-Ⅰ (prepared in Example 4), 1.57 g of tetrahydrofuran, 1.29 g of acetone, 5.065 g of N,N-dimethylformamide, 0.01 g of 1-hydroxycyclohexylphenyl ketone and 0.01 g of 4-dimethylaminopyridine, 0.005g p-aminopropiophenone mixed solution, with a power of 650W ultraviolet light illumination for 40min, thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 95 ° C for 10h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g surface functionalized regenerated carbon fiber cloth after drying was put into a mold, 0.25g HEP-12-Ⅰ (prepared in Example 4), 0.75g bisphenol A epoxy resin, 0.075g DOA, 0.05g DDS and 0.04g 3,4'-ODA mixture was evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot-pressed at 150 ° C for 2h under 8MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was carried out at 9MPa for 15min, and the temperature was taken out to achieve the degradation cycle recovery and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0114] Example 10 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0115] (1) Preparation of composite materials

[0116] 5.00 g of carbon fiber cloth (T300) was completely immersed in a mixed solution of 0.90 g of SH-HBP-8 (prepared in Example 3), 1.20 g of SH-HBP-6 (prepared in Example 2), 2.90 g of SH-HBP-20 (prepared in Example 7), 40 g of chloroform, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.04 g of benzophenone, 0.03 g of 4-dimethylaminopyridine, and 0.05 g of p-aminopropiophenone, and irradiated with ultraviolet light of 800 W for 20 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 10-TCF; 10-TCF was taken out and dried at 90° C. for 6 h; 4.00 g of 10-TCF after drying was taken out and placed in a mold, and 0.30 g of HEP-6 (prepared in Example 2), 0.20 g of A mixture of HEP-20 (prepared in Example 7), 0.80 g bisphenol A epoxy resin, 0.05 g DADPS, 0.05 g DDS, 0.10 g ODA and 0.10 g BAS was evenly applied to 10-TCF in the mold and hot-pressed and cured at 180 ° C for 1 h under 10 MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 15 MPa for 10 min. When the temperature dropped to 80 ° C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0117] (2) Degradation and recycling of composite materials

[0118] 5.00 g of the composite material was immersed in 16.00 g of 0.80 mol / L potassium hydroxide ethanol solution, and the carbon fiber cloth and degradation solution were obtained after degradation at 170° C. for 4 h; the carbon fiber cloth was rinsed with acetone and dried at 60° C. for 18 h to obtain a regenerated carbon fiber cloth; then 2.50 g of the regenerated carbon fiber cloth was completely immersed in 0.45 g of SH-HBP-8 (prepared in Example 3), 0.60 g of SH-HBP-6 (prepared in Example 2), 1.45 g of SH-HBP-20 (prepared in Example 7), 20 g of chloroform, 10 g of tetrahydrofuran, 40 g of ethyl acetate, 0.02 g of benzophenone and 0.015 g of 4-dimethylaminopyridine, 0.025g p-aminopropiophenone mixed solution, with 800W ultraviolet light illumination for 20min, thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 90 ° C for 6h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g of surface functionalized regenerated carbon fiber cloth after drying was put into a mold, 0.15g HEP-6 (prepared in Example 2), 0.10g HEP-20 (prepared in Example 7), 0.40g bisphenol A epoxy resin, 0.025g DADPS, 0.025g DDS and 0.05g ODA, 0.05g The BAS mixture is evenly applied to the functionalized recycled carbon fiber cloth on the mold surface, and hot-pressed and cured at 180°C for 1h under 10MPa conditions. After the hot pressing is completed, the heating is stopped, and the laminate is pressed at 15MPa for 10min. When the temperature reaches 80°C, it is taken out, and the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite materials can be achieved. The tensile strength is shown in Table 3.

[0119] Example 11 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0120] (1) Preparation of composite materials

[0121] 5.00 g of carbon fiber cloth (T700) was completely immersed in a mixed solution of 1.90 g of SH-HBP-6 (prepared in Example 2), 4.20 g of SH-HBP-8 (prepared in Example 3), 3.90 g of SH-HBP-24 (prepared in Example 8), 50 g of chloroform, 20 g of acetone, 80 g of ethyl acetate, 0.05 g of benzophenone, 0.04 g of 4-dimethylaminopyridine and 0.06 g of p-aminopropiophenone, and irradiated with ultraviolet light of 800 W for 20 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 11-TCF. The 11-TCF was taken out and dried at 100 ° C for 5 h. 4.00 g of 11-TCF after drying was taken out and placed in a mold, and 0.20 g of HEP-12-I (prepared in Example 4), 0.20 g of HEP-15 (prepared in Example 5), 0.40 g of A mixture of HEP-20 (prepared in Example 7), 0.80 g bisphenol A epoxy resin, 0.05 g ODA, 0.1 g DDS, 0.10 g 3,4'-ODA and 0.10 g BAS was evenly applied to 11-TCF in the mold and hot-pressed and cured at 180 ° C for 1 h under 10 MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 15 MPa for 10 min. When the temperature reached 80 ° C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0122] (2) Degradation and recycling of composite materials

[0123] 5.00g of the composite material was immersed in 20.00g of a mixed ethanol solution of 0.10mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 180°C for 2h; the carbon fiber cloth was rinsed with acetone and dried at 70°C for 10h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in 0.95g of SH-HBP-6 (prepared in Example 2), 2.10g of SH-HBP-8 (prepared in Example 3), 0.95g of SH-HBP-24 (prepared in Example 8), 25g of chloroform, 10g of acetone, 40g of ethyl acetate, 0.025g of benzophenone and 0.02g of 4-dimethylaminopyridine, 0.03g p-aminopropiophenone mixed solution, with 800W ultraviolet light illumination for 20min, thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 100 ° C for 5h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g of surface functionalized regenerated carbon fiber cloth after drying was put into a mold, 0.10g HEP-12-Ⅰ (prepared in Example 4), 0.10g HEP-15 (prepared in Example 5), 0.20g HEP-20 (prepared in Example 7), 0.40g bisphenol A epoxy resin, 0.025g ODA, 0.025g DDS and 0.025g 3,4'-ODA, 0.025g The BAS mixture is evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 10MPa conditions. After the hot pressing is completed, the heating is stopped, and the laminate is pressed at 15MPa for 10min. When the temperature reaches 80°C, it is taken out, and the degradation, recycling and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material can be achieved. The tensile strength is shown in Table 3.

[0124] Example 12 A high-performance biodegradable epoxy resin-carbon fiber composite material and a preparation method thereof, the steps of which are as follows:

[0125] (1) Preparation of composite materials

[0126] 4.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 1.50 g of SH-HBP-3 (prepared in Example 1), 1.51 g of SH-HBP-12-I (prepared in Example 4), 3.14 g of tetrahydrofuran, 2.58 g of acetone, 10.13 g of N,N-dimethylformamide, 0.02 g of 1-hydroxycyclohexyl phenyl ketone, 0.02 g of 4-dimethylaminopyridine, and 0.01 g of p-aminophenylacetone, and irradiated with ultraviolet light at a power of 650 W for 40 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 12-TCF; 12-TCF was taken out and dried at 95° C. for 10 h; 4.00 g of 12-TCF after drying was taken out and placed in a mold, and 0.31 g of HEP-6 (prepared in Example 2), 0.19 g of A mixture of HEP-8 (prepared in Example 3), 1.50g bisphenol A epoxy resin, 0.15g DOA, 0.1g DDS and 0.08g 3,4'-ODA was evenly applied to 11-TCF in the mold, and hot-pressed and cured at 150°C for 2h under 8MPa; after the hot pressing was completed, heating was stopped, and lamination was performed at 9MPa for 15min, and the temperature was taken out when it reached 80°C, thus obtaining a high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material. The tensile strength thereof is shown in Table 3.

[0127] (2) Degradation and recycling of composite materials

[0128] 5.00 g of the composite material was immersed in a mixed methanol aqueous solution (methanol: water = 9:1, m / m) of 12.00 g 0.42 mol / L potassium hydroxide and sodium hydroxide (potassium hydroxide: sodium hydroxide = 1:1, mol / mol), and the carbon fiber cloth and the degradation solution were obtained after degradation at 155 ° C for 9 h; the carbon fiber cloth was rinsed with acetone and dried at 65 ° C for 15 h to obtain a regenerated carbon fiber cloth; then 2.00 g of the regenerated carbon fiber cloth was completely immersed in 0.75 g SH-HBP-3 (prepared in Example 1), 0.755 g SH-HBP-12-Ⅰ (prepared in Example 4), 1.57 g tetrahydrofuran, 1.29 g acetone, 5.065 g N, N-dimethylformamide, 0.01 g 1-hydroxycyclohexylphenyl ketone and 0.01 g 4-dimethylaminopyridine, 0.005g p-aminopropiophenone mixed solution, with a power of 650W ultraviolet light for 40min, thiol-olefin click reaction, the carbon fiber cloth is taken out, and dried at 95°C for 10h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g surface functionalized regenerated carbon fiber cloth after drying is put into a mold, 0.155g HEP-6 (prepared in Example 2), 0.095g HEP-8 (prepared in Example 3), 0.75g bisphenol A type epoxy resin, 0.075g DOA, 0.05g DDS and 0.04g 3,4'-ODA mixture is evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot pressing and curing at 150°C for 2h under 8MPa conditions; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 9MPa for 15min, and when the temperature reaches 80°C, it is taken out, and the degradation cycle recovery and reuse of the high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material can be realized. The tensile strength is shown in Table 3.

[0129] Comparative Example 1:

[0130] 4.00 g of carbon fiber cloth (T300) was placed in a mold, and a mixture of 2.09 g of bisphenol A epoxy resin, 0.15 g of ODA and 0.10 g of 3,4'-ODA was evenly applied to the carbon fiber cloth in the mold, and hot-pressed and cured at 110 °C for 3 h under 3 MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 6 MPa for 19 min. When the temperature reached 80 °C, it was taken out to obtain an epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0131] Comparative Example 2:

[0132] 4.00 g of carbon fiber cloth (T700) was placed in a mold, and a mixture of 2.00 g of bisphenol A epoxy resin, 0.15 g of DOA, 0.1 g of DDS and 0.08 g of 3,4'-ODA was evenly applied to the carbon fiber cloth in the mold, and hot-pressed and cured at 150 °C for 2 h under 8 MPa conditions; after the hot pressing was completed, the heating was stopped, and the laminate was pressed at 9 MPa for 15 min. When the temperature reached 80 °C, it was taken out to obtain an epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0133] Comparative Example 3:

[0134] 4.00 g of carbon fiber cloth (T800) was placed in a mold, and a mixture of 1.30 g of bisphenol A epoxy resin, 0.06 g of DADPS, 0.02 g of DDS, 0.10 g of ODA, and 0.10 g of BAS was evenly applied to the carbon fiber cloth in the mold, and hot-pressed and cured at 180 ° C for 1 h under 9 MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 13 MPa for 12 min. When the temperature reached 80 ° C, it was taken out to obtain an epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0135] Comparative Example 4:

[0136] (1) Synthesis of hyperbranched epoxy resin

[0137] The preparation principles and processes of synthesized terminal thiol hyperbranched polymer DSPI-12 and hyperbranched epoxy resin DIHE-12 were based on the master's thesis of Xu Haifeng "Preparation and Performance Study of Imide Skeleton Hyperbranched Epoxy Resin / Carbon Fiber Composite Materials" (P18-19).

[0138] (2) Preparation of composite materials

[0139] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of DSPI-12, 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth. The surface functionalized carbon fiber cloth was taken out and dried at 85 ° C for 7 h. 4.00 g of the surface functionalized carbon fiber cloth after drying was put into a mold, and 1.30 g of DIHE-12, 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the surface functionalized carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 9MPa conditions. After the hot pressing was completed, the heating was stopped, and the laminated at 13MPa for 12min. When the temperature reached 80°C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0140] (3) Degradation and recycling of composite materials

[0141] 5.00g of the composite material was immersed in 15.00g of 0.11mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and the carbon fiber cloth and degradation solution were obtained after degradation at 160°C for 6h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 19h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.95g DSPI-12, 5g acetone, 10g tetrahydrofuran, 40g ethyl acetate, 0.015g benzophenone and 0.015g 4-dimethylaminopyridine, and 0.015g p-aminopropiophenone, and irradiated with ultraviolet light with a power of 750W for 30min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 85°C for 7h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.225g A mixture of DIHE-12, 0.425g bisphenol A epoxy resin, 0.03g DADPS, 0.01g DDS, 0.05g ODA and 0.05g BAS was evenly applied to the functionalized recycled carbon fiber cloth on the mold surface and hot-pressed and cured at 180°C for 1h under 9MPa conditions. After the hot pressing was completed, the heating was stopped and the laminated at 13MPa for 12min. When the temperature reached 80°C, it was taken out to achieve the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite materials. The tensile strength is shown in Table 3.

[0142] Comparative Example 5:

[0143] (1) Synthesis of hyperbranched epoxy resin

[0144] The preparation principles and processes of synthesized terminal thiol hyperbranched polymer DSPI-12 and hyperbranched epoxy resin DIHE-12 were based on the master's thesis of Xu Haifeng "Preparation and Performance Study of Imide Skeleton Hyperbranched Epoxy Resin / Carbon Fiber Composite Materials" (P18-19).

[0145] (2) Preparation of composite materials

[0146] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of DSPI-12, 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth. The surface functionalized carbon fiber cloth was taken out and dried at 85 ° C for 7 h. 4.00 g of the surface functionalized carbon fiber cloth after drying was put into a mold, and 0.45 g of DIHE-12, 0.85 g of bisphenol A epoxy resin, 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the surface functionalized carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 9MPa conditions. After the hot pressing was completed, the heating was stopped, and the laminated at 13MPa for 12min. When the temperature reached 80°C, it was taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0147] (3) Degradation and recycling of composite materials

[0148] 5.00g of the composite material was immersed in 15.00g of 0.11mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and the carbon fiber cloth and degradation solution were obtained after degradation at 160°C for 6h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 19h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.95g DSPI-12, 5g acetone, 10g tetrahydrofuran, 40g ethyl acetate, 0.015g benzophenone and 0.015g 4-dimethylaminopyridine, and 0.015g p-aminopropiophenone, and irradiated with ultraviolet light with a power of 750W for 30min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 85°C for 7h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.225g A mixture of DIHE-12, 0.425g bisphenol A epoxy resin, 0.03g DADPS, 0.01g DDS, 0.05g ODA and 0.05g BAS was evenly applied to the functionalized recycled carbon fiber cloth on the mold surface and hot-pressed and cured at 180°C for 1h under 9MPa conditions. After the hot pressing was completed, the heating was stopped and the laminated at 13MPa for 12min. When the temperature reached 80°C, it was taken out to achieve the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite materials. The tensile strength is shown in Table 3.

[0149] Comparative Example 6:

[0150] (1) Preparation of composite materials

[0151] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of SH-HBP-18 (prepared in Example 6), 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, i.e., 6-TCF; 6-TCF was taken out and dried at 85° C. for 7 h; 4.00 g of 6-TCF after drying was taken out and placed in a mold, and 1.30 g of HEP-18 (prepared in Example 6), 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the 6-TCF in the mold and hot-pressed and cured at 180°C for 1 h under 9 MPa. After the hot pressing was completed, the heating was stopped and the laminated at 13 MPa for 12 min. When the temperature reached 80°C, it was taken out to obtain an imide skeleton hyperbranched epoxy resin-carbon fiber composite material, the tensile strength of which is shown in Table 3.

[0152] (2) Degradation and recycling of composite materials

[0153] 5.00 g of the composite material was immersed in 15.00 g of 0.11 mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and degraded at 160°C for 6 h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 19 h to obtain a regenerated carbon fiber cloth; then 2.50 g of the regenerated carbon fiber cloth was completely immersed in 1.95 g of SH-HBP-18 (prepared in Example 6), 5 g of acetone, 10 g of tetrahydrofuran, 40 g of ethyl acetate, 0.015 g of benzophenone and 0.015 g of 4-dimethylaminopyridine, 0.015g p-aminopropiophenone mixed solution, with a power of 750W ultraviolet light illumination for 30min, thiol-olefin click reaction, the carbon fiber cloth is taken out, and dried at 85 ° C for 7h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g of surface functionalized regenerated carbon fiber cloth after drying is put into a mold, and a mixture of 0.65g HEP-18 (prepared in Example 6), 0.03g DADPS, 0.01g DDS and 0.05g ODA, 0.05g BAS is evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot-pressed and cured at 180 ° C for 1h under 9MPa conditions; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 13MPa for 12min, and the temperature is taken out to achieve the degradation cycle recovery and reuse of the degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0154] Comparative Example 7:

[0155] (1) Synthesis of hyperbranched epoxy resin

[0156] 2.00 g (10 mmol) 3,4'-ODA and 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 115°C for 10 h, and then 3.13 g (12 mmol) THEIC was added, stirred and reacted at 150°C for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 1.01 g (11 mmol) TGA, 2.65 g (25 mmol) MPA, 5.01 g xylene and 2 g toluene were added to the flask, and the stirring reaction was continued at 130°C for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-12-II), the number average molecular weight of which is shown in Table 1; finally 4.11 g (36 mmol) AGE and 0.02 g 4-Dimethylaminopyridine, 0.02g 2,2-dimethoxy-2-phenylacetophenone, 50.20g dichloromethane and 10.98g acetone were irradiated with ultraviolet light at a power of 550W for 40min to carry out a thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-12-II), the properties of which are shown in Table 2.

[0157] (2) Preparation of composite materials

[0158] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of SH-HBP-12-II (prepared in Comparative Example 7), 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, and the surface functionalized carbon fiber cloth was taken out and dried at 85 ° C for 7 h; 4.00 g of the surface functionalized carbon fiber cloth after drying was put into a mold, and 1.30 g of HEP-12-II (prepared in Comparative Example 7), 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the surface functionalized carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1 h under 9 MPa. After the hot pressing was completed, the heating was stopped, and the laminated at 13 MPa for 12 min. When the temperature reached 80°C, it was taken out to obtain an imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0159] (3) Degradation and recycling of composite materials

[0160] 5.00 g of the composite material was immersed in 15.00 g of 0.11 mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and degraded at 160 ° C for 6 h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 55 ° C for 19 h to obtain a regenerated carbon fiber cloth; then 2.50 g of the regenerated carbon fiber cloth was completely immersed in 1.95 g of SH-HBP-12-II (prepared in Comparative Example 7), 5 g of acetone, 10 g of tetrahydrofuran, 40 g of ethyl acetate, 0.015 g of benzophenone and 0.015 g of 4-dimethylaminopyridine, 0.015g p-aminopropiophenone mixed solution, with a power of 750W ultraviolet light illumination for 30min, thiol-olefin click reaction, the carbon fiber cloth is taken out, and dried at 85 ° C for 7h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g of surface functionalized regenerated carbon fiber cloth after drying is put into a mold, and a mixture of 0.65gHEP-12-II (prepared in Comparative Example 7), 0.03gDADPS, 0.01g DDS and 0.05gODA, 0.05g BAS is evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot-pressed and cured at 180 ° C for 1h under 9MPa conditions; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 13MPa for 12min, and the temperature is taken out to achieve the degradation cycle recovery and reuse of the degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0161] Comparative Example 8:

[0162] (1) Synthesis of hyperbranched epoxy resin

[0163] 2.16 g (10 mmol) BAS and 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 115° C. for 10 h, and then 3.13 g (12 mmol) THEIC was added, and stirred and reacted at 150° C. for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 1.01 g (11 mmol) TGA, 2.65 g (25 mmol) MPA, 5.01 g xylene and 2 g toluene were added to the flask, and the stirring reaction was continued at 130° C. for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-12-III), whose number average molecular weight is shown in Table 1; finally 4.11 g (36 mmol) AGE and 0.02 g 4-Dimethylaminopyridine, 0.02g 2,2-dimethoxy-2-phenylacetophenone, 50.20g dichloromethane and 10.98g acetone were irradiated with ultraviolet light of 550W for 40min to carry out thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-12-III), the properties of which are shown in Table 2.

[0164] (2) Preparation of composite materials

[0165] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of SH-HBP-12-III (prepared in Comparative Example 8), 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to carry out a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth, and the surface functionalized carbon fiber cloth was taken out and dried at 85 ° C for 7 h; 4.00 g of the surface functionalized carbon fiber cloth after drying was put into a mold, and 1.30 g of HEP-12-III (prepared in Comparative Example 8), 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the surface functionalized carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1 h under 9 MPa. After the hot pressing was completed, the heating was stopped, and the laminated at 13 MPa for 12 min. When the temperature reached 80°C, it was taken out to obtain an imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0166] (3) Degradation and recycling of composite materials

[0167] 5.00g of the composite material was immersed in 15.00g of 0.11mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and the carbon fiber cloth and the degradation solution were obtained after degradation at 160°C for 6h; the carbon fiber cloth was rinsed with acetone and dried at 55°C for 19h to obtain a regenerated carbon fiber cloth; then 2.50g of the regenerated carbon fiber cloth was completely immersed in a mixed solution of 1.95g SH-HBP-12-III (prepared in Comparative Example 8), 5g of acetone, 10g of tetrahydrofuran, 40g of ethyl acetate, 0.015g of benzophenone and 0.015g of 4-dimethylaminopyridine, and 0.015g of p-aminopropiophenone, and irradiated with ultraviolet light with a power of 750W for 30min to carry out a thiol-olefin click reaction, and the carbon fiber cloth was taken out and dried at 85°C for 7h to obtain a surface-functionalized regenerated carbon fiber cloth; 2.00g of the surface-functionalized regenerated carbon fiber cloth after drying was put into a mold, and 0.65g A mixture of HEP-12-III (prepared in Comparative Example 8), 0.03g DADPS, 0.01g DDS, 0.05g ODA and 0.05g BAS was evenly applied to the surface functionalized recycled carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1h under 9MPa conditions; after the hot pressing was completed, the heating was stopped, and the lamination was performed at 13MPa for 12min. When the temperature reached 80°C, it was taken out, and the degradation, recycling and reuse of the degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material could be achieved. The tensile strength is shown in Table 3.

[0168] Comparative Example 9:

[0169] (1) Synthesis of hyperbranched epoxy resin

[0170] 2.48 g (10 mmol) DDS and 3.84 g (20 mmol) TMA were added to a three-necked flask, stirred and reacted at 115° C. for 10 h, then 3.13 g (12 mmol) THEIC was added, stirred and reacted at 150° C. for 13 h to obtain a terminal hydroxyl hyperbranched polymer; 1.01 g (11 mmol) TGA, 2.65 g (25 mmol) MPA, 5.01 g xylene and 2 g toluene were added to the flask, and the stirring reaction was continued at 130° C. for 14 h to obtain a terminal thiol hyperbranched polymer (SH-HBP-12-IV), whose number average molecular weight is shown in Table 1; finally 4.11 g (36 mmol) AGE and 0.02 g 4-Dimethylaminopyridine, 0.02g 2,2-dimethoxy-2-phenylacetophenone, 50.20g dichloromethane and 10.98g acetone were irradiated with ultraviolet light of 550W for 40min to carry out thiol-olefin click reaction, and the solvent was removed to obtain a hyperbranched epoxy resin (HEP-12-IV), the properties of which are shown in Table 2.

[0171] (2) Preparation of composite materials

[0172] 5.00 g of carbon fiber cloth (T800) was completely immersed in a mixed solution of 3.90 g of SH-HBP-12-IV (prepared in Comparative Example 9), 10 g of acetone, 20 g of tetrahydrofuran, 80 g of ethyl acetate, 0.03 g of benzophenone, 0.03 g of 4-dimethylaminopyridine and 0.03 g of p-aminopropiophenone, and irradiated with ultraviolet light of 750 W for 30 min to perform a thiol-olefin click reaction to obtain a surface functionalized carbon fiber cloth. The surface functionalized carbon fiber cloth was taken out and dried at 85 ° C for 7 h; 4.00 g of the surface functionalized carbon fiber cloth after drying was put into a mold, and 1.30 g of HEP-12-IV (prepared in Comparative Example 9), 0.06 g of DADPS, 0.02 g of DDS and 0.10 g of ODA, 0.10 g of The BAS mixture was evenly applied to the surface functionalized carbon fiber cloth in the mold, and hot-pressed and cured at 180°C for 1 h under 9 MPa. After the hot pressing was completed, the heating was stopped, and the laminated at 13 MPa for 12 min. When the temperature reached 80°C, it was taken out to obtain an imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0173] (3) Degradation and recycling of composite materials

[0174] 5.00 g of the composite material was immersed in 15.00 g of 0.11 mol / L potassium hydroxide in methanol aqueous solution (methanol: water = 9:1, m / m), and degraded at 160° C. for 6 h to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth was rinsed with acetone and dried at 55° C. for 19 h to obtain a regenerated carbon fiber cloth; then 2.50 g of the regenerated carbon fiber cloth was completely immersed in 1.95 g of SH-HBP-12-IV (prepared in Comparative Example 9), 5 g of acetone, 10 g of tetrahydrofuran, 40 g of ethyl acetate, 0.015 g of benzophenone and 0.015 g of 4-dimethylaminopyridine, 0.015g p-aminopropiophenone mixed solution, with a power of 750W ultraviolet light illumination for 30min, thiol-olefin click reaction, the carbon fiber cloth was taken out, and dried at 85 ° C for 7h to obtain surface functionalized regenerated carbon fiber cloth; 2.00g of surface functionalized regenerated carbon fiber cloth after drying was put into a mold, and a mixture of 0.65g HEP-12-IV (prepared in Comparative Example 9), 0.03g DADPS, 0.01g DDS and 0.05g ODA, 0.05g BAS was evenly applied to the surface functionalized regenerated carbon fiber cloth in the mold, and hot-pressed and cured at 180 ° C for 1h under 9MPa conditions; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 13MPa for 12min, and the temperature is taken out to achieve the degradation cycle recovery and reuse of the degradable imide skeleton hyperbranched epoxy resin-carbon fiber composite material, and its tensile strength is shown in Table 3.

[0175] Table 1 Number average molecular weight of thiol-terminated hyperbranched polymers

[0176] Product Name Number average molecular weight (g / mol) SH-HBP-3 1300 SH-HBP-6 3100 SH-HBP-8 4200 SH-HBP-12-I 5900 SH-HBP-12-II 5700 SH-HBP-12-III 5600 SH-HBP-12-IV 5900 SH-HBP-15 6100 SH-HBP-18 8200 SH-HBP-20 10000 SH-HBP-24 16000

[0177] Table 2 Properties of degradable imide skeleton hyperbranched epoxy resins

[0178]

[0179]

[0180] Table 3 Tensile strength of hyperbranched epoxy resin / carbon fiber composites

[0181]

[0182] The number average molecular weight of the terminal thiol hyperbranched polymer obtained in Examples 1-12 is 1300-16000 g / mol, the number average molecular weight of the obtained degradable imide skeleton hyperbranched epoxy resin is 1500-19000 g / mol, the epoxy value is 0.10-0.25 mol / 100g, and the shape factor is 0.97-2.80.

[0183] The number average molecular weight is obtained by gel permeation chromatography (GPC) based on the permeation behavior of the hyperbranched polymer in the gel by measuring the permeation time and the ratio of the standard sample; the epoxy value is obtained by the hydrochloric acid-acetone method by using hydrochloric acid to destroy the epoxy group, and then determining the amount of the remaining hydrochloric acid by titration, and then knowing the amount of hydrochloric acid that reacts with the epoxy group, thereby calculating the amount of the epoxy group and obtaining the epoxy value; the shape factor is obtained by dynamic and static light scattering technology, and the mean square gyration radius (R g ), and the hydrodynamic radius (R h ), the ratio of the two (R g / R h ) is the shape factor.

[0184] In addition, it can be seen from the test results in Table 1 that the number average molecular weight of the terminal thiol hyperbranched polymers obtained in Examples 1-8 of the present invention gradually increases with the increase in the number of terminal thiol groups. When the number of terminal thiol groups is 24, the number average molecular weight reaches a maximum value of 16000 g / mol.

[0185] It can be seen from the test results in Table 2 that the epoxy resins obtained in Examples 1-8 of the present invention have a gradually increasing number of terminal epoxy groups, a gradually decreasing number average molecular weight, and a gradually decreasing epoxy value, and a trend of first decreasing and then increasing in shape factor, wherein when the number of terminal epoxy groups is 24, the number average molecular weight reaches a maximum of 19000 g / mol, and the epoxy value reaches a minimum of 0.10 mol / 100 g; when the number of terminal epoxy groups is 12, the shape factor is the minimum, which is 0.97. Through the shape factor data of the hyperbranched epoxy resins, it can be explained that the structures of the hyperbranched epoxy resins in the embodiments are all elliptical, wherein the shape factor value of HEP-12 is closest to 1, and its structure is the most regular, closer to a sphere.

[0186] From the test results in Table 3, we can see that:

[0187] The tensile strength of the composite materials obtained in Examples 1-12 is much higher than the tensile strength of the carbon fiber cloth in Comparative Examples 1-3, especially as shown in: Example 2 is significantly better than Comparative Example 1, Example 4 is significantly better than Comparative Example 2, and Example 6 is significantly better than Comparative Example 3. In these three groups, the carbon fiber cloth is modified by E51 resin only in the comparative example, while the carbon fiber cloth is modified by blending a special hyperbranched epoxy resin HEP ​​and E51 in the example, and the other steps and parameters are the same; in Comparative Example 6, a special hyperbranched epoxy resin HEP-18 is used to modify the carbon fiber cloth T800, and its tensile strength is higher than that of the carbon fiber cloth T800 modified by E51 resin (Comparative Example 3). However, the tensile strength of the composite material obtained in Example 6 is significantly better than that of Comparative Examples 3 and Comparative Example 6, proving that the blending system of hyperbranched epoxy resin and linear epoxy resin (epoxy resin E51) has the advantage of significantly improving the tensile strength of the composite material, which is much better than the tensile strength of the carbon fiber cloth composite material cured with a single resin.

[0188] The tensile strength of the composite material obtained in Example 9 is the highest, proving that HEP-12 has the best modification effect, which is consistent with the rule that the shape factor value of HEP-12 is closest to 1 in Table 2, and is consistent with the theory that the closer the shape factor is to 1, the more regular the structure of the hyperbranched epoxy resin is, and the better the performance is. It can also be seen from Comparative Example 6 and Comparative Examples 7, 8, and 9 that the modification effect of HEP-12 is better than that of HEP-18, which is mainly due to the difference in the structure of the hyperbranched resin, and the fundamental reason for the difference is the difference in the diamine monomers used in the synthetic resin. HEP-12 has a stronger interface interaction with carbon fiber and a better load transfer capacity, thereby having higher mechanical properties.

[0189] The tensile strength of the composite material obtained in Example 6 is much higher than that of the composite material obtained in Comparative Example 4, indicating that the tensile strength of the system of the present invention is improved compared with the previous invention system. Although the tensile strength of the composite material obtained in Comparative Example 5 is greatly improved compared with that of Comparative Example 4, it is still not as good as the tensile strength of the composite material obtained in Example 6.

[0190] The alkaline alcohol solution degradation system provided by the present invention can realize the degradation, recycling and reuse of high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite materials. The tensile strength of the composite material prepared by recycling the carbon fiber cloth recycled from the composite material is compared with the tensile strength of the original composite material, indicating that the tensile strength of the carbon fiber cloth recycled by degradation, recycling and recycling does not decrease significantly, and the retention rate is high.

[0191] And by comparing the data of comparative example 3 with that of example 1, it is shown that by adding the hyperbranched structure modification, the tensile strength of the carbon fiber cloth T300 can reach the tensile strength of the unmodified T800 or even exceed it.

[0192] In summary, the degradable imide skeleton hyperbranched epoxy resin of the present invention can significantly improve the tensile strength of the composite material, achieve the purpose of using low-grade carbon fiber to achieve the strength of high-grade carbon fiber, and at the same time realize the recycling of carbon fiber, and the tensile strength of the recycled carbon fiber cloth composite material does not decrease significantly.

[0193] Separation and recovery of monomers:

[0194] The degradation liquid of the composite material in Example 3 was filtered with a Buchner funnel, and the residue obtained after filtration and separation was a crude product of 3,3'-diaminodiphenyl sulfone, and the residue was purified by column chromatography to obtain recovered 3,3'-diaminodiphenyl sulfone, which was called RDADPS, with a recovery rate of about 52%. A new hyperbranched epoxy resin (RHER-8) was synthesized using RDADPS using the synthesis method in Example 3, and a hyperbranched epoxy resin / carbon fiber composite material was prepared according to the preparation method in Example 3. The tensile strength of the material was 721±12, and the tensile strength retention rate was 96%.

[0195] The tensile strength in Table 3 is measured by using a universal material testing machine (Instron 5943) in accordance with ASTM standard D3039 / D3039M-00 “Standard Test Method for Tensile Properties of Polymer-Based Composite Materials” at a test temperature of 25°C.

Claims

1. A high-performance degradable imide skeleton hyperbranched epoxy resin, characterized in that: Its structural formula is the following general formula (1): Wherein, R', R", and R'" are the same or different and are independently represented by the structure of general formula (2), general formula (3) or general formula (4): Wherein, X is one or two of the following structures: The structure of R1 is as follows: R2 is one of the following structures: R3 is one or more of the following structures: The number average molecular weight of the degradable imide skeleton hyperbranched epoxy resin is 1500-19000 g / mol, the epoxy value is 0.10-0.25 mol / 100 g, and the shape factor is 0.97-2.

80.

2. The method for preparing a high-performance degradable imide skeleton hyperbranched epoxy resin according to claim 1, characterized in that: Synthesized by the following steps: Add the diamino compound and the trianhydride compound into a three-necked flask, stir and react at 80-130°C for 8-12h, then add tris(2-hydroxyethyl)isocyanurate, stir and react at 120-180°C for 10-16h to obtain a terminal hydroxyl hyperbranched polymer; add mercaptocarboxylic acid and a water-carrying agent, continue stirring and reacting at 120-140°C for 10-16h to obtain a terminal mercapto hyperbranched polymer with a number average molecular weight of 1300-1600. 0g / mol; finally, add allyl glycidyl ether, an organic solvent and a photoinitiator into a three-necked flask, irradiate with ultraviolet light with a power of 400W-800W for 30-70min, carry out a thiol-olefin click reaction, and then remove the organic solvent to obtain a degradable imide skeleton hyperbranched epoxy resin with a number average molecular weight of 1500-19000g / mol, an epoxide value of 0.10-0.25mol / 100g, and a shape factor of 0.97-2.

80.

3. The method for preparing a high-performance degradable imide skeleton hyperbranched epoxy resin according to claim 2, characterized in that: The molar ratio of the diamino compound, the trianhydride compound, tris(2-hydroxyethyl)isocyanurate and mercaptocarboxylic acid is 1:2:(0.9-2):(1.5-8.5), and the molar ratio of mercaptocarboxylic acid to allyl glycidyl ether is 1:

1.

4. The method for preparing a high-performance degradable imide skeleton hyperbranched epoxy resin according to claim 3, characterized in that: The diamino compound is one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 2,2'-diaminodiphenyl sulfide, and 4,4'-diaminodiphenyl sulfide; the trianhydride compound is trimellitic anhydride or 1,2,4-cyclohexanetricarboxylic anhydride; and the mercaptocarboxylic acid is one or both of mercaptopropionic acid and mercaptoacetic acid.

5. The method for preparing a high-performance degradable imide skeleton hyperbranched epoxy resin according to claim 3, characterized in that: The water-carrying agent is one or two of toluene and xylene, and its mass is 0.5 to 5 times the mass of tris(2-hydroxyethyl)isocyanurate; the organic solvent is one or more of tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, chloroform, N,N-dimethylformamide and dichloromethane, and its mass is 10 to 30 times the mass of tris(2-hydroxyethyl)isocyanurate; the photoinitiator is one or more of 4-dimethylaminopyridine, benzophenone, p-aminopropiophenone, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycyclohexyl phenyl ketone, and its mass is 0.4% to 2% of the mass of allyl glycidyl ether.

6. A high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material, characterized in that: The degradable imide skeleton hyperbranched epoxy resin according to claim 1 or the degradable imide skeleton hyperbranched epoxy resin prepared by the method according to any one of claims 2 to 5 is blended with bisphenol A epoxy resin and filled into carbon fiber cloth, and then laminated and cured to obtain the obtained carbon fiber cloth; before curing, the carbon fiber cloth is modified by a thiol-olefin click reaction of a terminal mercapto hyperbranched polymer prepared by the method according to any one of claims 2 to 5 to obtain a surface functionalized carbon fiber cloth; preferably, the mass ratio of the carbon fiber cloth, the degradable imide skeleton hyperbranched epoxy resin and the bisphenol A epoxy resin is 1:(0.1-0.2):(0.2-0.5).

7. A method for preparing a high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material, characterized in that: The steps include: The carbon fiber cloth is completely immersed in a mixed solution of a terminal thiol hyperbranched polymer, an organic solvent and a photoinitiator prepared by the method described in any one of claims 2-5, and is illuminated with ultraviolet light with a power of 400W-800W for 20-60min to carry out a thiol-olefin click reaction; after the reaction is completed, the carbon fiber cloth is taken out and dried at 80-100°C for 5-15h to obtain a surface-functionalized carbon fiber cloth; the surface-functionalized carbon fiber cloth is placed in a mold, and a mixture of a degradable imide skeleton hyperbranched epoxy resin, a bisphenol A type epoxy resin and a curing agent prepared by the method described in any one of claims 2-5 is evenly applied to the surface-functionalized carbon fiber cloth, and hot-pressed and cured at 2-10MPa and 100-180°C for 1-3h; after the hot pressing is completed, the heating is stopped, and the lamination is carried out at 5-15MPa for 10-20min, and then the temperature is lowered to below 80°C and taken out to obtain a high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material; The number average molecular weight of the terminal thiol hyperbranched polymer is 1300-16000 g / mol, the number average molecular weight of the degradable imide skeleton hyperbranched epoxy resin is 1500-19000 g / mol, the epoxy value is 0.10-0.25 mol / 100 g, and the shape factor is 0.97-2.

80.

8. The method for preparing a high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material according to claim 7, characterized in that: The mass ratio of the surface functionalized carbon fiber cloth, the degradable imide skeleton hyperbranched epoxy resin, the bisphenol A type epoxy resin and the curing agent is 1: (0.1-0.2): (0.2-0.5): (0.05-0.1).

9. The method for preparing a high-performance biodegradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material according to claim 7, characterized in that: The carbon fiber cloth is one of commercially available T300, T700 and T800; the photoinitiator is one or more of 4-dimethylaminopyridine, benzophenone, p-aminopropiophenone, 2,2-dimethoxy-2-phenylacetophenone and 1-hydroxycyclohexylphenyl ketone, and the mass thereof is 0.5% to 3% of the mass of the carbon fiber cloth; the organic solvent is tetrahydrofuran, 1,4-dioxane, ethyl acetate, acetone, chloroform, N,N-dimethylformamide and dichloromethane. One or more of, whose mass is 0.5 to 30 times the mass of the carbon fiber cloth; the mass of the terminal thiol hyperbranched polymer is 0.5 to 2.0 times the mass of the carbon fiber cloth; the model of the bisphenol A type epoxy resin is E51; the curing agent is one or more of 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 2,2'-diaminodiphenyl sulfide, and 4,4'-diaminodiphenyl sulfide.

10. A degradation and recovery method for the high-performance degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material according to any one of claims 7 to 9, characterized in that: The steps include: The degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material according to any one of claims 7 to 9 is immersed in an alkaline alcohol solution, and degraded at 130-180° C. for 2-12 hours to obtain a carbon fiber cloth and a degradation solution; the carbon fiber cloth is rinsed with acetone and dried at 50-70° C. for 10-24 hours to obtain a regenerated carbon fiber cloth; and then the regenerated carbon fiber cloth is recycled by replacing the carbon fiber cloth according to the preparation method according to any one of claims 7 to 9; The concentration of the alkaline alcohol solution is 0.10-1.50 mol / L, the alkaline alcohol solution is an alcohol solution of potassium hydroxide and / or sodium hydroxide, the alcohol in the alkaline alcohol solution is methanol and / or ethanol, and preferably, the mass proportion of the alcohol in the alkaline alcohol solution is 90%-100%; Preferably, the mass ratio of the degradable imide skeleton hyperbranched epoxy resin / carbon fiber composite material to the alkaline alcohol solution is (3-5):(10-20).

Citation Information

Patent Citations

  • A sulfur-containing biodegradable hyperbranched epoxy resin and its preparation method

    CN108794726B

  • High temperature-resisting hyperbranched epoxy resin and preparation method thereof

    CN109320688A

  • Degradable hyperbranched epoxy resin and preparation method therefor

    WO2019206199A1

Cited By

  • Degradable epoxy resin composite material and preparation method thereof

    CN122060286A